Preparation method of BSL lubricating oil performance improving composite additive

By preparing composite additives, hexagonal boron nitride powder, nanocopper powder and graphene are used to solve the agglomeration problem of graphene in lubricating oil, improve the performance of lubricating oil, reduce friction and wear, and achieve better lubricating effect.

CN119899712AInactive Publication Date: 2025-04-29HAINAN KUNZHONG ENERGY GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411837403.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-29
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

As a lubricant additive, graphene is prone to agglomeration due to its high surface potential energy and easy to produce lubricant, resulting in insufficient performance, high friction coefficient and increased wear.

Method used

The preparation method of BSL lubricant oil performance enhancement composite additives is adopted to prepare composite additives by mixing hexagonal boron nitride powder, nanocopper powder, graphene, hydroxyethyl acrylate and dispersant in a specific proportion, and the composite additives are prepared by ultrasonic treatment, heating and stirring, centrifugal filtration and drying.

Benefits of technology

It effectively improves the performance of BSL lubricant, reduces the friction coefficient and wear spot area, changes the friction mode between the lubricant and moving objects, and changes from sliding friction to sliding and rolling composite friction, reducing friction and wear, and improving lubricating performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899712A_ABST
    Figure CN119899712A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lubricating oil additives, and discloses a preparation method of a BSL lubricating oil performance improving composite additive, which comprises the following steps: preparing hexagonal boron nitride powder, nano copper powder, graphene, hydroxyethyl acrylate and a dispersant; dissolving a dispersing agent in deionized water to obtain a dispersed aqueous solution; adding graphene and hydroxyethyl acrylate into an aqueous solution, and carrying out ultrasonic treatment to obtain an intermediate solution; heating and stirring the obtained intermediate solution in a reaction kettle to obtain a mixed solution; the preparation method of the composite additive for improving the performance of the BSL lubricating oil is easy and convenient to operate and easy to obtain, the obtained additive can effectively improve the performance of the BSL lubricating oil and is low in friction coefficient and small in wear scar area, the friction mode between the lubricating oil and a moving object can be changed by adding the hexagonal boron nitride powder, sliding friction is converted into sliding and rolling composite friction, and the service life of the lubricating oil is prolonged. Therefore, the frictional wear between the lubricating oil and a moving object is greatly reduced, and the antifriction property and lubricity of the lubricating oil are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lubricating oil additives, and in particular to a method for preparing a BSL lubricating oil performance-enhancing composite additive. Background Art

[0002] Lubricating oil is a liquid or semi-solid lubricant used in various types of automobiles and mechanical equipment to reduce friction and protect machinery and processed parts. It is indispensable in modern industry. In order to ensure the properties of lubricating oil, additives need to be added to lubricating oil to give the lubricant some new properties or improve some existing properties of the lubricant. As a new type of nano-carbon material, graphene has good mechanical properties, high thermal conductivity, etc. Its special two-dimensional sheet structure is conducive to reducing friction. Therefore, graphene is an ideal lubricant additive. However, due to its high surface potential energy, graphene is very easy to agglomerate and accumulate on the surface, which can easily cause sliding dry friction, increase wear, and the lubricant performance is insufficient. Therefore, it is very necessary to study a composite additive to improve the performance of lubricants. In view of this, an in-depth study was conducted on the above-mentioned issues, and a method for preparing a composite additive for improving the performance of BSL lubricating oil was proposed. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing a BSL lubricant performance improving composite additive to solve the problem that the existing additives for improving lubricant performance are poor as mentioned in the above background technology.

[0004] To achieve the above object, the present invention provides the following technical solution: a method for preparing a BSL lubricant performance improving composite additive, comprising the following steps: Step 1: prepare 10-20 parts of hexagonal boron nitride powder, 12-25 parts of nano copper powder, 30-40 parts of graphene, 30-40 parts of hydroxyethyl acrylate and 5-10 parts of dispersant; Step 2: dissolving the dispersant in deionized water to obtain a dispersed aqueous solution; Step 3: adding graphene and hydroxyethyl acrylate into a dispersed aqueous solution and subjecting it to ultrasonic treatment to obtain an intermediate solution; Step 4: placing the obtained intermediate solution in a reaction kettle and heating and stirring to obtain a mixed solution; Step 5: dissolving hexagonal boron nitride powder and nano copper powder in deionized water to obtain a powder aqueous solution; Step 6: Add the powder aqueous solution into the reaction kettle and stir and mix with the mixed solution to obtain a mixture; Step 7: subjecting the mixture to ultrasonic treatment, and then centrifugally filtering and drying to obtain a composite additive.

[0005] As a preferred technical solution of the present invention, the dispersant in step 1 is one of a titanate coupling agent, a tin coupling agent and a silicon coupling agent.

[0006] As a preferred technical solution of the present invention, the thickness of the graphene in step 1 is 2 to 4 nm.

[0007] As a preferred technical solution of the present invention, in step three, the frequency of ultrasonic treatment is controlled to be 20 to 40 kHz, and the time is 40 to 50 minutes.

[0008] As a preferred technical solution of the present invention, in step 4, the temperature of the reactor is controlled at 150-160° C., the pressure is controlled at 1-5 MPa, the stirring speed is controlled at 400-600 r / min, and the stirring time is controlled at 20-30 min.

[0009] As a preferred technical solution of the present invention, in step six, the reactor is heated to 180-200° C., and after being evacuated, the stirring speed is controlled to 800-1000 r / min, and the stirring time is 25-40 min.

[0010] As a preferred technical solution of the present invention, in step seven, the frequency of the ultrasonic treatment is controlled to be 50-60 KHz and the time is 20-30 minutes.

[0011] As a preferred technical solution of the present invention, in step seven, the centrifugal speed is controlled to be 8000-10000 rpm, and the centrifugal time is 15-20 min.

[0012] As a preferred technical solution of the present invention, in step seven, the drying temperature is controlled to be 90-110° C., and the drying time is 1.5-4.5 hours.

[0013] Compared with the prior art, the beneficial effects of the present invention are as follows: the preparation method of the BSL lubricant performance improving composite additive is simple and easy to operate, the obtained additive can effectively improve the performance of the BSL lubricant, and has a low friction coefficient and a small wear spot area. The addition of hexagonal boron nitride powder can change the friction mode between the lubricant and the moving object from sliding friction to sliding and rolling composite friction, thereby greatly reducing the friction and wear between the lubricant and the moving object, and improving the friction reduction and lubricity of the lubricant. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a performance test data chart of the additive prepared by the present invention after being added to BSL lubricating oil. DETAILED DESCRIPTION

[0015] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Embodiment 1

[0016] See also Figure 1 The technical solution of the present invention is: a method for preparing a BSL lubricant performance improving composite additive, comprising the following steps: Step 1: prepare 10 parts of hexagonal boron nitride powder, 12 parts of nano copper powder, 30 parts of graphene, 30 parts of hydroxyethyl acrylate and 5 parts of dispersant; Step 2: dissolving the dispersant in deionized water to obtain a dispersed aqueous solution; Step 3: adding graphene and hydroxyethyl acrylate into a dispersed aqueous solution and subjecting it to ultrasonic treatment to obtain an intermediate solution; Step 4: placing the obtained intermediate solution in a reaction kettle and heating and stirring to obtain a mixed solution; Step 5: dissolving hexagonal boron nitride powder and nano copper powder in deionized water to obtain a powder aqueous solution; Step 6: Add the powder aqueous solution into the reaction kettle and stir and mix with the mixed solution to obtain a mixture; Step 7: subjecting the mixture to ultrasonic treatment, and then centrifugation filtration and drying to obtain a composite additive; The dispersant in step 1 is one of a titanate coupling agent, a tin coupling agent and a silicon coupling agent.

[0017] The thickness of the graphene in step 1 is 2 nm; In step 3, the frequency of ultrasonic treatment is controlled to be 20KHz and the time is 50min; In step 4, the temperature of the reactor is controlled at 150°C, the pressure is 1 MPa, the stirring speed is controlled at 400 r / min, and the stirring time is controlled at 30 min; In step 6, the reactor is heated to 180°C, and after being evacuated, the stirring speed is controlled to 800r / min and the stirring time is 40min; In step 7, the frequency of ultrasonic treatment is controlled to be 50KHz and the time is 30min; Wherein in step 7, the centrifugal speed is controlled to be 8000 rpm and the centrifugal time is 20 min; In step 7, the drying temperature is controlled to be 90° C. and the drying time is 4.5 hours. Embodiment 2

[0018] See also Figure 1 The technical solution of the present invention is: a method for preparing a BSL lubricant performance improving composite additive, comprising the following steps: Step 1: prepare 10 parts of hexagonal boron nitride powder, 15 parts of nano copper powder, 30 parts of graphene, 30 parts of hydroxyethyl acrylate and 7 parts of dispersant; Step 2: dissolving the dispersant in deionized water to obtain a dispersed aqueous solution; Step 3: adding graphene and hydroxyethyl acrylate into a dispersed aqueous solution and subjecting it to ultrasonic treatment to obtain an intermediate solution; Step 4: placing the obtained intermediate solution in a reaction kettle and heating and stirring to obtain a mixed solution; Step 5: dissolving hexagonal boron nitride powder and nano copper powder in deionized water to obtain a powder aqueous solution; Step 6: Add the powder aqueous solution into the reaction kettle and stir and mix with the mixed solution to obtain a mixture; Step 7: subjecting the mixture to ultrasonic treatment, and then centrifugation filtration and drying to obtain a composite additive; The dispersant in step 1 is one of a titanate coupling agent, a tin coupling agent and a silicon coupling agent.

[0019] The thickness of the graphene in step 1 is 2 nm; In step 3, the frequency of ultrasonic treatment is controlled to be 20KHz and the time is 50min; In step 4, the temperature of the reactor is controlled at 155°C, the pressure is controlled at 2MPa, the stirring speed is controlled at 450r / min, and the stirring time is controlled at 25min; In step 6, the reactor is heated to 180°C, and after being evacuated, the stirring speed is controlled to 850r / min and the stirring time is 40min; In step 7, the frequency of ultrasonic treatment is controlled to be 50KHz and the time is 30min; Wherein in step 7, the centrifugal speed is controlled to be 8000 rpm and the centrifugal time is 20 min; In step 7, the drying temperature is controlled to be 95° C. and the drying time is 4 hours. Embodiment 3

[0020] See also Figure 1 The technical solution of the present invention is: a method for preparing a BSL lubricant performance improving composite additive, comprising the following steps: Step 1: prepare 15 parts of hexagonal boron nitride powder, 15 parts of nano copper powder, 30 parts of graphene, 32 parts of hydroxyethyl acrylate and 7 parts of dispersant; Step 2: dissolving the dispersant in deionized water to obtain a dispersed aqueous solution; Step 3: adding graphene and hydroxyethyl acrylate into a dispersed aqueous solution and subjecting it to ultrasonic treatment to obtain an intermediate solution; Step 4: placing the obtained intermediate solution in a reaction kettle and heating and stirring to obtain a mixed solution; Step 5: dissolving hexagonal boron nitride powder and nano copper powder in deionized water to obtain a powder aqueous solution; Step 6: Add the powder aqueous solution into the reaction kettle and stir and mix with the mixed solution to obtain a mixture; Step 7: subjecting the mixture to ultrasonic treatment, and then centrifugation filtration and drying to obtain a composite additive; The dispersant in step 1 is one of a titanate coupling agent, a tin coupling agent and a silicon coupling agent.

[0021] The thickness of the graphene in step 1 is 3 nm; In step 3, the frequency of ultrasonic treatment is controlled to be 25KHz and the time is 45min; In step 4, the temperature of the reactor is controlled at 155°C, the pressure is controlled at 2MPa, the stirring speed is controlled at 450r / min, and the stirring time is controlled at 25min; In step 6, the reactor is heated to 190°C, and after being evacuated, the stirring speed is controlled to 900r / min and the stirring time is 30min; In step 7, the frequency of ultrasonic treatment is controlled to be 55KHz and the time is 250min; Wherein in step 7, the centrifugal speed is controlled to be 9000 rpm and the centrifugal time is 18 min; In step 7, the drying temperature is controlled to be 100° C. and the drying time is controlled to be 3.5 hours. Embodiment 4

[0022] See also Figure 1 The technical solution of the present invention is: a method for preparing a BSL lubricant performance improving composite additive, comprising the following steps: Step 1: prepare 15 parts of hexagonal boron nitride powder, 20 parts of nano copper powder, 35 parts of graphene, 35 parts of hydroxyethyl acrylate and 8 parts of dispersant; Step 2: dissolving the dispersant in deionized water to obtain a dispersed aqueous solution; Step 3: adding graphene and hydroxyethyl acrylate into a dispersed aqueous solution and subjecting it to ultrasonic treatment to obtain an intermediate solution; Step 4: placing the obtained intermediate solution in a reaction kettle and heating and stirring to obtain a mixed solution; Step 5: dissolving hexagonal boron nitride powder and nano copper powder in deionized water to obtain a powder aqueous solution; Step 6: Add the powder aqueous solution into the reaction kettle and stir and mix with the mixed solution to obtain a mixture; Step 7: subjecting the mixture to ultrasonic treatment, and then centrifugation filtration and drying to obtain a composite additive; The dispersant in step 1 is one of a titanate coupling agent, a tin coupling agent and a silicon coupling agent.

[0023] The thickness of the graphene in step 1 is 3 nm; In step 3, the frequency of ultrasonic treatment is controlled to be 40KHz and the time is 40min; In step 4, the temperature of the reactor is controlled at 160°C, the pressure is controlled at 3MPa, the stirring speed is controlled at 500r / min, and the stirring time is controlled at 25min; In step 6, the reactor is heated to 200°C, and after being evacuated, the stirring speed is controlled to 950r / min and the stirring time is 30min; In step 7, the frequency of ultrasonic treatment is controlled to be 60KHz and the time is 22min; Wherein in step 7, the centrifugal speed is controlled to be 9500 rpm and the centrifugal time is 18 min; In step 7, the drying temperature is controlled to be 100° C. and the drying time is controlled to be 3 hours. Embodiment 5

[0024] See also Figure 1 The technical solution of the present invention is: a method for preparing a BSL lubricant performance improving composite additive, comprising the following steps: Step 1: prepare 20 parts of hexagonal boron nitride powder, 20 parts of nano copper powder, 35 parts of graphene, 70 parts of hydroxyethyl acrylate and 9 parts of dispersant; Step 2: dissolving the dispersant in deionized water to obtain a dispersed aqueous solution; Step 3: adding graphene and hydroxyethyl acrylate into a dispersed aqueous solution and subjecting it to ultrasonic treatment to obtain an intermediate solution; Step 4: placing the obtained intermediate solution in a reaction kettle and heating and stirring to obtain a mixed solution; Step 5: dissolving hexagonal boron nitride powder and nano copper powder in deionized water to obtain a powder aqueous solution; Step 6: Add the powder aqueous solution into the reaction kettle and stir and mix with the mixed solution to obtain a mixture; Step 7: subjecting the mixture to ultrasonic treatment, and then centrifugation filtration and drying to obtain a composite additive; The dispersant in step 1 is one of a titanate coupling agent, a tin coupling agent and a silicon coupling agent.

[0025] The thickness of the graphene in step 1 is 4 nm; Wherein the frequency of the ultrasonic treatment in step 3 is controlled to be 40KHz and the time is 400min; In step 4, the temperature of the reactor is controlled at 160°C, the pressure is controlled at 4 MPa, the stirring speed is controlled at 600 r / min, and the stirring time is controlled at 20 min; In step 6, the reactor is heated to 200°C and evacuated to make it hollow, and the stirring speed is controlled to be 1000r / min and the stirring time is 25min. In step 7, the frequency of ultrasonic treatment is controlled to be 60KHz and the time is 20min; Wherein in step 7, the centrifugal speed is controlled to be 9500 rpm and the centrifugal time is 15 min; In step 7, the drying temperature is controlled to be 110° C. and the drying time is controlled to be 2 hours. Embodiment 6

[0026] See also Figure 1 The technical solution of the present invention is: a method for preparing a BSL lubricant performance improving composite additive, comprising the following steps: Step 1: prepare 20 parts of hexagonal boron nitride powder, 25 parts of nano copper powder, 40 parts of graphene, 40 parts of hydroxyethyl acrylate and 10 parts of dispersant; Step 2: dissolving the dispersant in deionized water to obtain a dispersed aqueous solution; Step 3: adding graphene and hydroxyethyl acrylate into a dispersed aqueous solution and subjecting it to ultrasonic treatment to obtain an intermediate solution; Step 4: placing the obtained intermediate solution in a reaction kettle and heating and stirring to obtain a mixed solution; Step 5: dissolving hexagonal boron nitride powder and nano copper powder in deionized water to obtain a powder aqueous solution; Step 6: Add the powder aqueous solution into the reaction kettle and stir and mix with the mixed solution to obtain a mixture; Step 7: subjecting the mixture to ultrasonic treatment, and then centrifugation filtration and drying to obtain a composite additive; The dispersant in step 1 is one of a titanate coupling agent, a tin coupling agent and a silicon coupling agent.

[0027] The thickness of the graphene in step 1 is 4 nm; In step 3, the frequency of ultrasonic treatment is controlled to be 40KHz and the time is 40min; In step 4, the temperature of the reactor is controlled at 160°C, the pressure is controlled at 5 MPa, the stirring speed is controlled at 600 r / min, and the stirring time is controlled at 20 min; In step 6, the reactor is heated to 200°C and evacuated to make it hollow, and the stirring speed is controlled to be 1000r / min and the stirring time is 25min; In step 7, the frequency of ultrasonic treatment is controlled to be 60KHz and the time is 20min; Wherein in step 7, the centrifugal speed is controlled to be 10000 rpm and the centrifugal time is 15 min; In step 7, the drying temperature is controlled to be 110° C. and the drying time is 1.5 hours.

[0028] Comparative Example 1 The difference between this solution and Example 6 is that except for not adding hexagonal boron nitride powder, the rest is the same.

[0029] Comparative Example 2 The difference between this solution and Example 6 is that except for not adding nano copper powder, the rest is the same.

[0030] test: The additives obtained in the above examples and comparative examples were added into the BSL lubricating oil, and the mass ratio of the additives to the BSL lubricating oil was 1:200. The friction and wear tester was used to test the test results. Figure 1 As shown in the data, it can be seen that the friction coefficient in the embodiments is less than 0.020, and the wear spot area is less than 3.50*1.80mm 2 In comparative example 1, the friction coefficient and the wear spot area are much larger than those in the embodiment. Therefore, the addition of hexagonal boron nitride powder can effectively reduce the friction coefficient and the wear spot area and improve the lubrication performance. In comparative example 2, the friction coefficient and the wear spot area are slightly larger than those in the embodiment. Nano copper powder has a certain effect of reducing the friction coefficient and the wear spot area.

[0031] The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.

[0032] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a BSL lubricant performance enhancing composite additive, characterized in that: The following steps are involved: Step 1: prepare 10-20 parts of hexagonal boron nitride powder, 12-25 parts of nano copper powder, 30-40 parts of graphene, 30-40 parts of hydroxyethyl acrylate and 5-10 parts of dispersant; Step 2: dissolving the dispersant in deionized water to obtain a dispersed aqueous solution; Step 3: adding graphene and hydroxyethyl acrylate into a dispersed aqueous solution and subjecting it to ultrasonic treatment to obtain an intermediate solution; Step 4: placing the obtained intermediate solution in a reaction kettle and heating and stirring to obtain a mixed solution; Step 5: dissolving hexagonal boron nitride powder and nano copper powder in deionized water to obtain a powder aqueous solution; Step 6: Add the powder aqueous solution into the reaction kettle and stir and mix with the mixed solution to obtain a mixture; Step 7: subjecting the mixture to ultrasonic treatment, and then subjecting it to centrifugal filtration and drying to obtain a composite additive.

2. The method for preparing the BSL lubricating oil performance improving composite additive according to claim 1, characterized in that: In the step 1, the dispersant is one of a titanate coupling agent, a tin coupling agent and a silicon coupling agent.

3. The method for preparing the BSL lubricating oil performance improving composite additive according to claim 2, characterized in that: In the step 1, the thickness of the graphene is 2-4 nm.

4. The method for preparing the BSL lubricating oil performance improving composite additive according to claim 1, characterized in that: In the step 3, the frequency of the ultrasonic treatment is controlled to be 20-40 KHz, and the time is 40-50 min.

5. The method for preparing the BSL lubricating oil performance improving composite additive according to claim 1, characterized in that: In the step 4, the temperature of the reactor is controlled at 150-160° C., the pressure is controlled at 1-5 MPa, the stirring speed is controlled at 400-600 r / min, and the stirring time is controlled at 20-30 min.

6. The method for preparing the BSL lubricating oil performance improving composite additive according to claim 1, characterized in that: In the step 6, the reactor is heated to 180-200° C., and after being evacuated, the stirring speed is controlled to be 800-1000 r / min, and the stirring time is 25-40 min.

7. The method for preparing the BSL lubricating oil performance improving composite additive according to claim 1, characterized in that: In step seven, the frequency of ultrasonic treatment is controlled to be 50-60 KHz, and the time is 20-30 minutes.

8. The method for preparing the BSL lubricating oil performance improving composite additive according to claim 1, characterized in that: In step seven, the centrifugal speed is controlled to be 8000-10000 rpm, and the centrifugal time is 15-20 min.

9. The method for preparing the BSL lubricating oil performance improving composite additive according to claim 1, characterized in that: In step seven, the drying temperature is controlled to be 90-110° C., and the drying time is controlled to be 1.5-4.5 hours.